Radioactivity evaluation and radiation dosimetry assessment in Greek honey. (15th November 2022) - Xarchoulakos, Dimitrios C.; Lasithiotakis, Michael
Highlights: A radioactivity research regarding Greek honeys was performed for the first time. Alpha spectrometry measurements did not affect by the matrix due to the used dissolution techniques. 210 Pb was determined in honeys for the first time and is a good indicator for the presence of 210 Po. 137 Cs was detected in six samples. This is of significant importance since it is an index of nuclear fallout. Greek honeys are safe to consume for all age groups. Abstract: Greek honey was examined for 238 U, 234 U, 210 Pb, 210 Po, 40 K, and 137 Cs levels. 238 U was calculated from 0.013 ± 0.007 Bq kg −1 to 0.10 ± 0.02 Bq kg −1 while 234 U ranged from 0.017 ± 0.009 Bq kg −1 to 0.11 ± 0.03 Bq kg −1 . 210 Pb measured from 0.04 ± 0.02 Bq kg −1 to 1.70 ± 0.26 Bq kg −1 whereas 210 Po activity determined between 0.02 ± 0.01 Bq kg −1 and 2.31 ± 0.34 Bq kg −1 . 40 K found at the range of 7.9 ± 1.6 Bq kg −1 to 102.2 ± 19.7 Bq kg −1 and 137 Cs 0.3 ± 0.1 Bq kg −1 up to 0.8 ± 0.1 Bq kg −1 . Uranium isotopes and 210 Po were determined via alpha spectrometry. 210 Pb was also indirectly determined by alpha spectrometry. 40 K and 137 Cs were measured through γ-ray spectrometry. An annual dose calculation was performed for different age groups.